Textbook grammar in focus: A study of sentence structures and patterns alignment - Laela Nur Muktasida; Yuliati (ELT Forum: Journal of English Language Teaching, 2025)
Understanding the grammatical structures of sentences is fundamental for English learners. It concerns not only the forms, but also the meaning and usage. This comprehensive approach helps to transmit grammatical concepts effectively; thus, learners are directly influenced to communicate competently. This study aims to analyze the sentence structures and patterns, and the alignment of sentences in the texts with the targeted language features. The research employed a qualitative approach, especially textual analysis. Data were collected from five representative texts across five units of the textbook. This study differs from previous research by examining the alignment of sentence from the texts in a currently used curriculum-based textbook with targeted language features, and utilizing labeled bracketing to depict the structures more precisely. The findings reveal that the textbook uses a wide range of sentence structures to support different genres and text functions. From the five texts, the sentences show a wide range of pattern variations. There are complex declarative with complement or relative clauses, SVC patterns with prepositional elaborations, and verb-initial passive imperative complemented by temporal adjuncts, and so on. The most dominant phrase is complex noun phrase. Representative texts in Units 2, 3, and 4 fully align with the grammar and vocabulary outlined in the scope and sequence, while those in Units 1 and 5 show only partial alignment. This study contributes to the evaluation of EFL textbooks by examining the variation of sentence structures and patterns, and investigating their alignment with the targeted language features for supporting effective language acquisition.